Determinants of adjustment among Malaysian repatriates - Mohd.Yusoff, Yusliza (2004)
Repatriates’ adjustment is widely researched particularly in America, Finland, and Japan. A growing body of research has been carried out to study on its determinants and outcomes. The present study intended to contribute to the Malaysian literature pertaining to this subject. The purpose of the present study is to determine the impact of individual variable (self-efficacy), job variables (role clarity, role conflict, role discretion, and role novelty), organizational variable (social support), and non-work variable (culture novelty) on three dimensions of repatriates’ adjustment (psychological well-being, socio-cultural re-adjustment, and work re-adjustment).